L’essere-in-sé della prassi-processo: limitazione esterna dell’interiorità e limitazione interna dell’esteriorità (Nóema, 2019)
Extract from the italian translation of "Critique of Dialectical Reason Volume 2: The Intelligibility of History" by Jean-Paul Sartre ("Critica della ragione dialettica, Tomo II: L’intelligibilità della storia", italian translation by F. Cambria, Christian Marinotti Edizioni, Milano 2006, pp. 409-426).Italian translationFrench text
Keywords: Sartre; Critique of Dialectical Reason Volume 2; The Intelligibility of History; materialism